A Bilateral Advantage for Storage in Visual Working Memory - Umemoto, Akina (2010)
Various studies have demonstrated enhanced visual processing when information is presented across both visual hemifields rather than in a single hemifield (the bilateral advantage). For example, reported that observers were able to track twice as many moving visual stimuli when the tracked items were presented bilaterally rather than unilaterally, suggesting that independent resources enable tracking in the two visual fields. Motivated by similarities in the apparent capacity and neural substrates that mediate tracking and visual working memory (WM), the present work examined whether or not a bilateral advantage also arises during storage in visual WM. Using a recall procedure to assess working memory for orientation information, we found a reliable bilateral advantage; recall error was smaller with bilateral sample displays than with unilateral displays. To demonstrate that the bilateral advantage influenced storage per se rather than just encoding efficiency, we replicated the observed bilateral advantage using sequentially presented stimuli. Finally, to further characterize how bilateral presentations enhanced storage in working memory, we measured both the number and the resolution of the stored items and found that bilateral presentations lead to an increased probability of storage, rather than enhanced mnemonic resolution. Thus, the bilateral advantage extends beyond the initial selection and encoding of visual information to influence online maintenance in visual working memory.